Development of information and analytical procurement methodology of public administration in the sphere of providing civil control over the sector of security and defense of Ukraine - Salnikova, Olha; Marutian, Rena; Vereschak, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2023)
The problem that is solved in the research is to increase the efficiency of decision making in management tasks while ensuring the given reliability, regardless of the hierarchy of the system. The object of the research is the decision making support system in the field of democratic civilian control over the security and defense sector (FDCCSDS). The subject of research is the decision making process in management tasks using fuzzy cognitive maps and evolving artificial neural networks. The hypothesis of the research is to increase the number of sources of information about the components of the FDCCSDS, with restrictions on the efficiency and reliability of decision making. The research proposed a method for evaluating the information and analytical provision of public administration in FDCCSDS. It was established that the proposed method has a higher efficiency compared to the known ones by an average of 40 %, compared to the methods used to evaluate the effectiveness of strategic management decisions. The specified method will make it possible to assess the state of information and analytical provision of public administration in the FDCCSDS and to determine effective measures to improve efficiency. The method will allow to analyze possible options for the development of FDCCSDS in each phase of development and moments in time when it is necessary to carry out structural changes that ensure the transition to the next phase. At the same time, subjective factors of choice are taken into account while searching for solutions, which are formalized in the form of weighting coefficients for the components of the integral criterion of efficiency. The specified method allows to increase the speed of assessment of the state of information and analytical support of the FDCCSDS, to reduce the use of computing resources of and decision making support systems, to form measures aimed at increasing the efficiency of information and analytical support